Reproducing, disrupting and reforming understanding of cultural diversity: theorising future subject teachers' pedagogical reflections. Issue 3 (3rd July 2019) - Niemi, Pia-Maria; Hahl, Kaisa
ABSTRACT: Despite the growing demands for carrying out intercultural education as part of all teaching and learning, little attention has been given to the ways in which future subject teachers understand the meaning of 'cultural diversity' and how teacher education programmes prepare future teachers to consider intercultural aims in education. Therefore, this study investigates how future subject teachers, studying in an international teacher education programme in Finland, conceptualise the educational aims related to cultural diversity in reflective group discussions. For theorising the student teachers' reflections, this study applies the idea of cultural reproduction depicted in the theory of communicative action by Habermas as an analytical framework for identifying how student teachers reach agreement or disagreement in issues regarding educational aims related to cultural diversity. This study identified three main forms of cultural reproduction from the student teachers' discussions and showed that the underlying understanding about 'cultural diversity' and the educational aims related to it are in a state of disruption. This study highlights the need to clarify the theoretical concepts and aims used to guide intercultural education and to further emphasise issues of cultural diversity during teacher education. The findings are important for developing practices within subject teacher education internationally.